Tinjauan Material High-Performance sebagai Nosel Roket: Nickel Superalloy, Refractory Metals, CMCs, dan C-C Composites - Setyanjana, Andre Yoan; Yogaswara, Y. H; Marsono, Marsono; Junjunan, Soleh Fajar (Fakultas Teknik UMSU, 2025)
The advancement of rocket propulsion technology relies heavily on the development and optimization of high-performance materials capable of withstanding the extreme conditions inside rocket nozzles. This review comprehensively discusses four major material classes for rocket nozzles: Nickel-Based Superalloys, Refractory Metals, Ceramic Matrix Composites (CMCs), and Carbon-Carbon (C-C) Composites. This review highlights the unique properties, advantages, and limitations of each material in rocket nozzle applications using the Systematic Literature Review research method. Nickel-Based Superalloys are renowned for their outstanding high-temperature strength and oxidation resistance, but face challenges in terms of density and cost, thus requiring improvements in composition and processing techniques. Refractory Metals such as tungsten, molybdenum, and tantalum have very high melting points and thermal conductivity, but brittleness and oxidation at high temperatures are major constraints, requiring further research into coatings and alloying strategies. CMCs, mainly based on silicon carbide (SiC), offer high thermal stability, low density, and resistance to thermal shock. However, CMCs materials are also prone to oxidation at high temperatures and rely heavily on fiber-matrix interactions, requiring exploration of manufacturing methods for structural integrity under dynamic thermal loads. Whereas, C-C Composites excel in thermal resistance and light weight, ideal for nozzle throats and exit cones, they are prone to oxidation, requiring protective coatings and treatments to enhance their longevity in oxidative environments.